Metabolic and bariatric surgery reduces aging biomarkers in patients with obesity, independently of achieving optimal total weight loss - Alicja Dudek; Barbara Zapała; Ilona Kawa; Karol Ciszek; Piotr Tylec; Katarzyna Cyranka; Michał Wysocki; Piotr Major (Videosurgery and Other Miniinvasive Techniques)
Introduction: Obesity, a chronic disease linked to premature aging, is increasingly managed through metabolic and bariatric surgery (MBS).